Establishing and restructuring marketing channels: An exploratory study of a Taiwanese company in Russia - Wen-shinn Low; Soo-may Cheng (Journal for East European Management Studies, 2009)
The rise of emerging markets not only provides opportunities for business growth but also for academic researchers to explore different paradigms in international marketing activities. This article details a case study of how a Taiwanese mother board company establishes and re-structures marketing channels in Russia over three developmental stages: entry, accelerating growth and decelerating growth stages. The findings reflect that market mechanism cannot be fully developed in the entry and accelerating growth stages due to obstacles to distributor selection and limited resources of supplier. Different growth speeds between channels necessitate the supplier to re-structure its channel partnerships. – – Der Aufstieg der 'emerging markets' bietet nicht nur Chancen für Geschäftsund Unternehmenswachstum, sondern gibt auch Wissenschaftlern die Gelegenheit, verschiedene Paradigmen bezüglich internationalen Marketing- Aktivitäten zu untersuchen. Dieser Artikel beinhaltet die Fallstudie eines taiwanesischen Motherboard-Herstellers und den Aufbau bzw. die Restrukturierung seiner Absatzwege in Russland anhand von drei Entwicklungsstufen: Markteinstieg, beschleunigtes Wachstum und verlangsamtes Wachstum. Die Ergebnisse zeigen, dass sich der Marktmechanismus auf den Stufen Markteinstieg und beschleunigtes Wachstum nicht vollständig entwickeln kann, aufgrund von Hindernissen bei der Auswahl der Absatzmittlern und begrenzten Ressourcen der Lieferanten. Unterschiedliche Wachstumgeschwindigkeiten zwischen verschiedenen Absatzwegen erfordern vom Lieferanten die Umstrukturierung seiner Partnerschaften.
Keywords: 650; Marketing channel; Channel re-structuring; Emerging markets; Russia